Kelayakan Bisnis Percetakan Syailendra Kota Palangkaraya Ditinjau Dari Aspek Pemasaran - Nurlia Eka Damayanti; Cristian David; Elisabet Maria Rensiana Anggae; Norol Aisyah; Grecia Yunita; Owen Juniarko; Putri Dahlia (Lembaga Pengembangan Kinerja Dosen, 2024)
This study was conducted to determine whether a printing business should be established in Palangkaraya. The data sampled in this study is qualitative primary data. The collection of all data required in this study was carried out through the interview method. According to Esterberg in Sugiyono (2020:114) an interview is a meeting of two people to exchange information and ideas through questions and answers, so that meaning can be contributed to a particular topic